Experimental Study on the Sliding Friction and Wear Characteristics of Roller Burnished Polymers - Ong, L. K.; El-Tayeb, N. S. M.; Brevern, P. V. (CARL HANSER VERLAG, 2008)
The increasing utilization of polymers in sliding members has triggered much research on the enhancement of surface quality and tribological performance. In this regard, no work has considered the application of roller burnishing as a new surface treatment method for polymeric surfaces. The present work aims to investigate the influence of burnishing feed and roller contact width on the sliding friction and wear performance of acetal homopolymer and polyurethane. Dry and lubricated sliding conditions for both parallel and crossed burnished orientations were considered. The results revealed that low burnishing feed rate and smaller roller contact width led to a decrease in coefficient of friction for both polymers while improvement in the wear resistance was observed. Hence, it can be suggested that the roller burnishing process has high potential as a valuable polymer surface treatment technique.